THE EFFECT OF EXPERIENTIAL MARKETING AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT MCDONALD’S MANADO - Tangkuman, Miraldha Jane; Massie, James D.D.; Mangantar, Maryam M (Universitas Sam Ratulangi, 2020)
Abstract: In a rapidly developing era, there are many fast-food restaurants developing in Indonesia, an increasingly modern human lifestyle has led to the growing needs of consumers today. In Manado itself is one of the big cities in Indonesia. As a big city that continues to develop, the rate of development and change globally is also accelerating. The food and beverage business is currently growing and in great demand by business people. After observing the culture, residents in Manado are happy to gather and chat while enjoying the dishes provided in several places. Such as fast food restaurants, beverage shops, café nuances of restaurants, or small tented cafes that are increasingly mushrooming everywhere. The purpose of this study is to find out whether The Effect Of Experiential Marketing and Customer Satisfaction on Customer Loyalty at McDonald’s Manado. This research implies quantitative method, to achieve this goal the researchers distributed questionnaires and samples used 97 respondents. The results of this study indicate that experiential marketing has a significant positive effect on customer loyalty but customer satisfaction has a positive but not significant effect on customer loyalty. Keywords: experiential marketing, customer satisfaction, customer loyalty